A rare diagnosis of nasal mass: extramedullary plasmacytoma - Kamath, Shrinath; Pratap, Deepika; Shetty, Kishore Chandra; ., Biniyam (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2018)
Extramedullary plasmacytomas (EMPs) are localized plasma cell neoplasms that occur within the soft tissue. Solitary plasmacytoma of the head and neck is a rare disease entity. They account for 1–2% of all plasma cell growths and have a great predilection for the upper respiratory tract. Males are more frequently affected during the fifth and sixth decades of life. We report a case of maxillary sinus plasmacytoma in an elderly man. Complete resolution of the tumour was seen with radiotherapy.